Pollutant removal and acute toxicity assessment (Artemia salina) of landfill leachate treated by photo-Fenton process mediated by oxalic acid. (April 2019) - Borba, Fernando H.; Leichtweis, Jandira; Bueno, Francine; Pellenz, Leandro; Inticher, Jonas J.; Seibert, Daiana
Highlights: The photo-Fenton reaction was mediated by an organic complexing agent. The complexing agent avoids precipitation of pollutants during the acidification. A reactor using a SUNTEST system was employed. An increase in the biodegradability was observed. The degradation of pollutants promoted a toxicity reduction. Abstract: In this research, the application of the organic complexing agent oxalic acid in photo-Fenton reaction was assessed in the treatment of landfill leachate, using a lab scale photoreactor with coupled UVvis - irradiation. The operational parameters [Fe 3+ ] and initial pH were studied in central composite rotatable design, and assessed through a response surface methodology. The best operational conditions were observed at pH 7.8 and 90 mg Fe 3+ L −1, with around 5.8 kJ L −1 accumulated energy and consumption of approximately 220 Mm of H2 O2, obtaining reductions of 52.5 and 47.0% in color and Abs 254 nm, respectively. A high efficiency of the mediated photo-Fenton process as a function of the accumulated energy profile (0.0–9.8 kJ L −1 ) was observed, with significant reductions of biochemical oxygen demand, chemical oxygen demand, total dissolved carbon and dissolved organic carbon, as well as an increase in the biodegradability ratio. Additionally, a high degradation of several molecular structures present in the landfill leachate was observed via gas chromatography–mass spectrometry, which was associated with the low toxicity of the treated effluent (LC50 of 67%), showed by the Artemia salina bioassays. Thus, the mediated photo-Fenton process presented a high efficiency in the reduction of the toxic effects of the landfill leachate, contributing with the minimization of the environmental impacts caused by its discharge in soils or water bodies.